(untitled) (Anclajes, 2021)
The presence of late 19th century scientific positivism is evident in novels by Roque Larraquy (especially La comemadre, 2010) and Iosi Havilio (Opendoor, 2006 and Paraísos, 2011), set in part or entirely in the 21st century. I argue that Larraquy finds a narrative tone and character type in turn-of-the-century institutions and archives, whereas Havilio procures a motivation for a protagonist otherwise devoid of passions. For both novelists, the archive functions more as a narrative device than as a search for knowledge or meaning (as it does in boom novels). In this way, both the institutions created in the late 19th century (a psychiatric residence, a hospital, a zoo) and the textual remnants of the time (a botanical encyclopedia, an inaugural speech in a fin-de-siècle ward, a travel narrative, the magazine Caras y Caretas) are retrieved in these contemporary novels through light affective responses, such as curiosity and interest, and spaces of serendipity and abandonment, like the attic.